Experiential Learning Model for the Development of Collaborative Skills through Project Based Learning Practicum - Muhammad Hasan; Nur Arisah; Ratnah S; Muhammad Ihsan Said Ahmad; Miranda (Jurnal Pendidikan Indonesia, 2023)
To be able to improve student learning outcomes and to build a pleasant learning atmosphere, teachers need to design learning well, one way is to apply an experience-based learning model so that students can develop their collaboration skills which are one of the important skills and are needed in the 21st century. This study aims to analyze the implementation model of experiential learning in developing collaboration skills of Vocational High School students through practicum-based project-based learning. This study used a mixed methods approach. The informants in this study were 3 teachers and 22 students of vocational high school as respondents. The data obtained in this study were collected using interviews and questionnaires. The data analysis technique uses a Sequential Exploratory Design. The results of this study indicate that (1) teachers have implemented experience-based learning for students through project-based practicum; and (2) experience-based learning through project-based practicum makes teachers and students feel that this learning model plays an important role in developing student collaboration skills that can be implemented in everyday life.